Būdvardžių su priesagomis -ingas (-a), -inis (-ė) ir -iškas (-a) istoriniai ryšiai - Ambrazas, Saulius (Baltistica, 2002)
HISTORICAL RELATIONS OF ADJECTIVES WITH THE SUFFIXES -ingas (-a), -inis (-ė) AND -iškas (-a) Derivatives in -ingas (-a) (< *-ino- +*-g-)were much more productive in Old Lithuanian than in Modern Lithuanian. In the 16th–17th centuries they were widely formed not only from substantives but also from adjectives (cf. dosningas MP 96; K1G 63; C I 708 : dosnùs ‘generous, liberal’), verbs (cf. geidingas ‘desirous’ SP I 35919-20: geĩsti ‘desire’) and sometimes from participles, cf. išganytingas ‘salutary’ (widely used in Old Lithuanian texts): išganýtas ‘saved’. The same derivational features are characteric of adjectives in *-ingo- in Latvian, partly in Old Prussian and of corresponding derivatives with the suffix *-ino- in the Baltic languages. Some Old Lithuanian adjectives in -ingas (-a) had the same meaning as their equivalents with the suffixes -inas (cf. kruvingas KN 25114 and krùvinas ‘bloody’), -inis (cf. akmeningas DP 687 and akmenìnis ‘of stones’), -iškas (dievingas SD3 232 and diẽviškas ‘divine’). Adjectives in -iškas (-a) were also semanticaly very close to derivatives in -inis (-ė) in the texts of the 16th–17th centuries, cf. example from „Ewangelie Polskie y Litewskie” (1647) by J. Jaknavičius: tewas iuʃu dungißkas (aba dunginis) peniiuos 11313-16. So in Old Lithuanian denominative derivatives in -ingas (-a), -inas (-a), -inis (-ė)and -iškas (-a) belonged to the same derivational category of attributive adjectives. On the other hand, deverbal derivatives in -ingas (-a), -inas (-a), -tinas (-a) and other deverbal adjectives can be ascribed to another derivational category – adjectives denoting actions and their results.